Critically analysing a grand coaltion cabinet ( GCC) as a temporary solution to democracy in Africa : a case of Zimbabwe (2009-2013) - Blessed, Hondo (Midlands State University, 2020)
The study aims to unravel the temporal resolutions and stability brought by the emergency of Grand Coalition Cabinet (GCC), popularly known as the Government of national unity (GNU) in Zimbabwe. The research dwells much on different temporary economic, political and social developments and improvements brought up by GCC during states’ economic, political and social chaotic and meltdown era from 2008 -2013.The researcher would be looking at how problems and crises which were prevailing before signing of the Grant coalition cabinet (GCC)